2019
DOI: 10.1111/evo.13680
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary pathways toward gigantism in sharks and rays

Abstract: Through elasmobranch (sharks and rays) evolutionary history, gigantism evolved multiple times in phylogenetically distant species, some of which are now extinct. Interestingly, the world's largest elasmobranchs display two specializations found never to overlap: filter feeding and mesothermy. The contrasting lifestyles of elasmobranch giants provide an ideal case study to elucidate the evolutionary pathways leading to gigantism in the oceans. Here, we applied a phylogenetic approach to a global dataset of 459 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 84 publications
6
69
0
Order By: Relevance
“…suggests that this individual has not reached maturity at band pair 25 with an estimated body size between 369 and 607cm. These estimations are reasonable when compared to modern giant sharks ("gigantism" sensu Pimiento et al [81] refers to sharks with body sizes exceeding six meters), which show similar sizes at maturity, e.g., the great white shark, Carcharodon carcharias, at 350-500cm (TL about 600cm), basking shark, Cetorhinus maximus, at 400-800cm (TL more than 1000cm), whale shark, Rhincodon typus, at 600-800cm (TL 1700-2100cm) [2]. When compared to big macropredatory sharks (i.e., great white shark Carcharodon carcharias and Cretoxyrhina mantelli), it is apparent that the slope of the growth curve of †Ptychodus is less steep and more similar to the microphagous basking shark Cetorhinus maximus ( Fig 5C).…”
Section: Plos Onesupporting
confidence: 67%
“…suggests that this individual has not reached maturity at band pair 25 with an estimated body size between 369 and 607cm. These estimations are reasonable when compared to modern giant sharks ("gigantism" sensu Pimiento et al [81] refers to sharks with body sizes exceeding six meters), which show similar sizes at maturity, e.g., the great white shark, Carcharodon carcharias, at 350-500cm (TL about 600cm), basking shark, Cetorhinus maximus, at 400-800cm (TL more than 1000cm), whale shark, Rhincodon typus, at 600-800cm (TL 1700-2100cm) [2]. When compared to big macropredatory sharks (i.e., great white shark Carcharodon carcharias and Cretoxyrhina mantelli), it is apparent that the slope of the growth curve of †Ptychodus is less steep and more similar to the microphagous basking shark Cetorhinus maximus ( Fig 5C).…”
Section: Plos Onesupporting
confidence: 67%
“…Although the exact phylogenetic relatedness of †O. megalodon and its family to the order Lamniformes remains poorly understood 21,22,25 , our chosen analogue taxa are the most ecologically and physiologically similar living species to †O. megalodon.…”
Section: Discussionmentioning
confidence: 99%
“…These same methods were used for otodontids and the results suggested similar thermoregulatory capabilities 24 . Moreover, a phylogenetic analysis of the evolution of thermophysiology in this group found that mesothermy had likely evolved once in the Cretaceous 25 . Based on these studies, we considered otodontids to be mesothermic.…”
Section: Methodsmentioning
confidence: 98%
“…We then tested whether rates of molecular substitution differed on branches leading to gigantism in vertebrates when compared to the background rate of molecular evolution in vertebrates. The origins of gigantism in elephants, whales, and whale sharks has previously been shown to correspond to shifts in the rate or mode of body size evolution [56][57][58] . We estimated time-varying rates of body size evolution in cartilaginous fishes, and consistent with previous research 58 , found that gigantism in whale shark corresponds to a discrete shift in the rate of body size evolution to five times the background in cartilaginous fishes (Supplementary Note 4; Supplementary Figure 6) 58 .…”
Section: Evolution Of Innate Immunity In the Whale Sharkmentioning
confidence: 99%
“…The origins of gigantism in elephants, whales, and whale sharks has previously been shown to correspond to shifts in the rate or mode of body size evolution [56][57][58] . We estimated time-varying rates of body size evolution in cartilaginous fishes, and consistent with previous research 58 , found that gigantism in whale shark corresponds to a discrete shift in the rate of body size evolution to five times the background in cartilaginous fishes (Supplementary Note 4; Supplementary Figure 6) 58 . We thus compared rates of genomic evolution in vertebrate giantsrepresented by African elephant, minke whale, bowhead whale, and whale shark -to other vertebrates.…”
Section: Evolution Of Innate Immunity In the Whale Sharkmentioning
confidence: 99%